Evaluasi Efektivitas PPh 25 dalam Meningkatkan Pendapatan Pajak dan Mengurangi Beban Pajak pada Wajib Pajak - Sapwan Sapik Nasution; Azzahra Dinda Aulia; Zaki Maulana (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This study aims to evaluate the effectiveness of the implementation of Income Tax Article 25 (PPh 25) in increasing state tax revenue and reducing the tax burden on taxpayers. PPh 25 is a mechanism for periodic tax installment payments made by taxpayers based on estimated tax liabilities. This research adopts a descriptive quantitative approach using secondary data obtained from the Directorate General of Taxes’ reports, supported by questionnaires distributed to taxpayers within a specific Tax Service Office (KPP) area. The results show that the implementation of PPh 25 contributes significantly to tax revenue by encouraging taxpayer compliance and ensuring a stable cash flow for the state. Additionally, the installment system of PPh 25 helps reduce the annual tax burden on taxpayers both psychologically and administratively, as obligations are paid in stages. However, challenges remain in the accuracy of estimating tax liabilities, which can lead to overpayment or underpayment. Therefore, more intensive socialization and technical guidance are needed to improve taxpayers’ understanding and compliance with the PPh 25 mechanism.